2013
DOI: 10.1371/journal.pone.0064777
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Vagus Nerve in the Migrating Motor Complex and Ghrelin- and Motilin-Induced Gastric Contraction in Suncus

Abstract: The upper gastrointestinal (GI) tract undergoes a temporally coordinated cyclic motor pattern known as the migrating motor complex (MMC) in both dogs and humans during the fasted state. Feeding results in replacement of the MMC by a pattern of noncyclic, intermittent contractile activity termed as postprandial contractions. Although the MMC is known to be stimulated by motilin, recent studies have shown that ghrelin, which is from the same peptide family as motilin, is also involved in the regulation of the MM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 40 publications
1
49
0
Order By: Relevance
“…Furthermore, in contrast to rats and mice, it also expresses motilin (39). However, in the same species it has been shown that motilin induces phase III contractions independently of the vagus nerve via a myenteric cholinergic neural pathway (40,41). It is unclear whether the administration of a low dose of erythromycin is still able to induce a phase III contraction in vagotomized patients.…”
Section: Figurementioning
confidence: 99%
“…Furthermore, in contrast to rats and mice, it also expresses motilin (39). However, in the same species it has been shown that motilin induces phase III contractions independently of the vagus nerve via a myenteric cholinergic neural pathway (40,41). It is unclear whether the administration of a low dose of erythromycin is still able to induce a phase III contraction in vagotomized patients.…”
Section: Figurementioning
confidence: 99%
“…Recently, we found that motilin but not ghrelin stimulate gastric acid secretion in a dose dependent manner (manuscript preparation), and the intravenous administration of motilin causes gastric phase-III like contractions in suncus [22]. Gastric acid and pepsinogen secretion increase during the late phase II and phase III [23], and the higher luminal acid concentration leads to an increase in pepsinogen secretion in humans [24].…”
Section: Introductionmentioning
confidence: 95%
“…The body temperature of anesthetized suncus was monitored using a midi logger GL220 (Graphtec, Japan) and maintained at 35e38 C. In order to stabilize the amount of pepsinogen secreted, we allowed 60 min from the start of the saline perfusion before commencing effluent tube collection continuously at 10-min intervals using a DF-2000 fraction collector (Tokyo Rikakikai Co., Ltd., Tokyo, JAPAN). For experiments using vagotomized suncus, a truncal subdiaphragmatic vagotomy was performed as described previously [22]. In brief, the lower part of the esophagus was exposed to isolate the dorsal and ventral vagus nerves.…”
Section: Determination Of Pepsin Output Using An Intragastric Perfusimentioning
confidence: 99%
“…The role of ghrelin on the migratory motor complex (MMC) has also been studied in several animal models to show stimulation of phase II of the MMC via the vagus nerve in the house musk shrew, Suncus murinus [52] and induction of a fasted motor pattern, enhancing motility of the antrum and duodenum in the fed or fasted state of healthy rodents [53][54][55][56].…”
Section: Effects Of Ghrelin On Gastrointestinal Motilitymentioning
confidence: 99%